Konsep Pemasaran dalam Sudut Pandang Ekonomi Islam - Hafidz Ainur Rofi; Adi Mansah (CV Edujavare Publishing, 2024)
Marketing is an important aspect in the business world because it maintains the principle of balancing products or services with customers. Over the decades, concept marketing has experienced significant growth and is now considered an integral part of modern business strategy. The aim of this research is to highlight the basic principles of the Islamic viewpoint that are very important for business operations. The methods used include data reduction, data analysis, and prediction of conclusions using quantitative means. The research results show that the concept of sales from an Islamic perspective can also be called sales in a sharia context. In the context of sharia, the concept of sales is different from the conventional one, especially in business transactions, which are based on the principles applied. In sharia marketing, business activities are carried out in accordance with Islamic principles, including the Koran and Hadith, to ensure the fulfillment of faith.